New modification of the Perkow reaction: halocarboxylate anions as leaving groups in 3-acyloxyquinoline-2,4(1H,3H)-dione compounds - Paleta, Oldřich; Pomeisl, Karel; Kafka, Stanislav; Klásek, Antonín; Kubelka, Vladislav (Beilstein Journal of Organic Chemistry, 2005)
Substituted 3-(fluoroacyloxy)quinoline-2,4(1H,3H)-diones including 3-(fluoroiodoacetoxy) derivatives react with triethyl phosphite to afford either the product of the Perkow reaction or the corresponding 4-ethoxyquinolin-2(1H)-one. In both reactions, the fluorocarboxylate anion acts as the first observed leaving group. This observation restricts the application of the intramolecular Horner-Wadsworth-Emmons synthesis to modify quinoline-2,4(1H,3H)-diones by the annulation of fluorinated but-2-enolide rings.